Influence of Food Additives on Children's Behavioral Patterns in Vietnam - Xuan, Anh (American Journal of Food Sciences and Nutrition, 2024)
Purpose: The aim of the study was to assess the influence of food additives on children's behavioral patterns in Vietnam. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that that certain food additives, such as artificial colors and preservatives, may contribute to hyperactivity and attention deficits in children. However, the evidence is not conclusive, with some studies indicating no significant impact on behavior. Factors such as individual sensitivity, dosage, and interaction with other dietary components may also play a role. Overall, while there is some indication of a potential link between food additives and behavioral changes, more research is needed to fully understand the extent of this relationship and its implications for children's health. Implications to Theory, Practice and Policy: Biopsychosocial model, social learning theory and gene-environment interaction theory may be used to anchor future studies on assessing the influence of food additives on children's behavioral patterns in Vietnam. In terms of practical applications, it is crucial to implement age-specific interventions and educational programs targeting parents, caregivers, and healthcare professionals. From a policy perspective, advocating for stricter regulations and guidelines regarding the use of food additives, particularly in products marketed to children, is paramount.